Building the «true evolutionism»: Darwin's impact on Henri Bergson's thought - Costa Carvalho, Magda (2014)
The paper focuses on the importance of Darwin’s work for the shaping of Henri Bergson’s philosophy, bearing on mind that the two authors first intercepted symbolically in 1859, when On the Origin of Species was published and Bergson was born. Bergson studied the biological sciences of his time, whose results were integrated in a metaphysical thought. He belonged to spiritualistic positivism, a philosophy that goes from the positive data of sciences and finds the ultimate explanation of reality in a spiritual principle. He was interested in the positive evolution of the natural world and in the works of naturalists such as Lamarck, De Vries or Eimer. Darwin was among these authors, being responsible for a vision of evolution that went from the scientific level to other domains. Bergson defends the “insufficiency of pure Darwinism” by pointing out the necessity to compensate scientific evolution with an internal metaphysical reading of the real, which he considered to be “true evolutionism”. This criticism is the most visible aspect of the relations between both works. However, an attentive look verifies that Darwin’s influence overcomes the divergence of positions concerning the extent of “evolution”. The French philosopher knew not only the 1859’s bestseller, but also studies by Darwin about ethology, entomology and botany, which contributed to the fact that the naturalist’s impact gained fundamental importance in Bergson’s philosophical perspective.